The Mediating Role of Psychological Empowerment on the Relationship between Person Fit Organization and Knowledge Sharing Behavior in Innovative Work Behavior - Ratnasari, Erna; Sudarma, Ketut (Management Analysis Journal, 2019)
The purpose of this study was to determine the effect of person organization fit and knowledge sharing behavior on the innovative work behavior through psychological empowerment as mediation, The population in this study were all employees of PT Telekomunikasi Seluler Central Java Regional DIY totaling 115 employees. Sampling using sampling nonproballity saturated samples. Methods of data collection is done by using questionnaires. The analytical method datamenggunakan regression analysis and path analysis with the help of analytical tools IBM SPSS version 21. The results showed that there is a direct effect of a positive and significant correlation betweenperson organization fit and knowledge sharing behavior on the innovative work behavior, The results also show the effect of indirect relationships are positive and significant correlation between person organization fit and knowledge sharing behavior on the innovative work behavior through psychological empowerment as mediation,